Priority of AIDC Implementation in AirNav Indonesia's ATS System Using AHP Method - Liber Tommy Hutabarat; Inda Tri Pasa; Robi Saputra; Morist Sony; Agung Pramono (Dinasti Review, 2026)
This study aims to provide decision-making support to AirNav Indonesia regarding the prioritization of AIDC (Air Traffic Services Inter-Facility Data Communication) implementation across its western region branches. The research is grounded in AirNav Indonesia's vision to modernize its ATS system, specifically through AIDC implementation, to enhance flight services and global connectivity with neighboring countries. The Analytical Hierarchy Process (AHP) method was employed, utilizing purposive sampling of ATS System specialists from six AirNav Indonesia branches in the western region. The data was analyzed following the AHP method’s hierarchical structure, including criteria, sub-criteria, and alternatives. The key criteria assessed were infrastructure readiness, ATC workload, human resources readiness, traffic volume, and number of connections. The alternatives were the JATSC, Medan, Pekanbaru, Palembang, Pontianak, and Tanjung Pinang branches. The research findings indicate that JATSC ranked first in priority for AIDC implementation, with a global sub-criterion weight of 0.3648, followed by Medan (0.3109), Palembang (0.3061), Pekanbaru (0.2829), Tanjung Pinang (0.2825), and Pontianak (0.1585). The ATS System specialists, who are directly involved with AIDC equipment, provided objective assessments, as evidenced by all criteria and sub-criteria having consistency ratios below 0.1, indicating acceptable consistency. It is recommended that AIDC implementation at AirNav Indonesia be carried out in phases and continued over time, considering available resources, to improve air traffic services and achieve global flight connectivity with neighboring countries.